2001
DOI: 10.1021/jp010179f
|View full text |Cite
|
Sign up to set email alerts
|

α,α-Trehalose/Water Solutions. 5. Hydration and Viscosity in Dilute and Semidilute Disaccharide Solutions

Abstract: We report viscosity and compressibility measurements of trehalose, maltose, and sucrose aqueous solutions at different concentration and temperature values. What emerges from the concentration dependence of viscosity and compressibility is that trehalose, in comparison to maltose and sucrose, shows a higher interaction strength with water, which gives rise to a greater value of the hydration number throughout the investigated temperature range. Furthermore, viscosity measurements reveal that at high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
113
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 32 publications
(68 reference statements)
29
113
0
3
Order By: Relevance
“…Then the water molecules constructing the ice Ic would slightly interact with disaccharide molecules even though they are not bound to the disaccharide molecules directly. The transition temperature from ice Ic to ice Ih was around 240 K which coincides well with the vitrification temperature (T g ') of the disaccharide solution; T g ' was approximately 238 K, 234 K and 233 K for the 50 wt% concentration of the trehalose, sucrose and maltose solutions, respectively (Branca et al, 2001). This is also the case for T g '=230 K of glucose Thanatuksora et al, 2008) and for the eutectic point of 67 wt% glycerol at 230 K (Vigier et al, 1987;Berejnov et al, 2006).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Then the water molecules constructing the ice Ic would slightly interact with disaccharide molecules even though they are not bound to the disaccharide molecules directly. The transition temperature from ice Ic to ice Ih was around 240 K which coincides well with the vitrification temperature (T g ') of the disaccharide solution; T g ' was approximately 238 K, 234 K and 233 K for the 50 wt% concentration of the trehalose, sucrose and maltose solutions, respectively (Branca et al, 2001). This is also the case for T g '=230 K of glucose Thanatuksora et al, 2008) and for the eutectic point of 67 wt% glycerol at 230 K (Vigier et al, 1987;Berejnov et al, 2006).…”
supporting
confidence: 65%
“…In Figure 7, several reported viscosities measured using the conventional techniques are presented simultaneously. Most of the bulk viscosities of disaccharide solutions were measured by mechanical viscometers: the Ubbelohde viscometer (Magazù et al, 1999;Elieas & Elias, 1999;Branca et al, 2001), the Marion-Krieger Sisco capillary viscometer (Matsuoka et al, 2002), or the rotational viscometer (Nagasawa et al, 2003). The selected literature data plotted in Figure 7 were measured in a temperature range of 293.2-313.2 K. Viscosities of other disaccharide solutions, sucrose (η suc ) and maltose (η mal ), were found to be similar to that of η treha at a given concentration within the experimental uncertainties (shown in Figure 7).…”
Section: Freezing Properties Of Disaccharide Solutions: Inhibition Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences emerge on D w only at 66 wt %, at which the numbers of waterwater and water-sugars HBs are comparable. Then, D w is found the lowest in the trehalose solution, as could be expected from its larger hydration number [18,26,27]. [41] for pure water and from Rampp et al [39] in 10, 30, 50 and 60 wt % trehalose solutions are also reported as a triangle and stars symbols, respectively.…”
Section: Water Translational Diffusion Coefficientsmentioning
confidence: 58%
“…Therefore, their bioprotective effect is thought to partially stem from the significant slowing down they induce on the dynamics of protein hydration water molecules [15,16,17]. Indeed, sugars form numerous hydrogen bonds (HBs) with water [18,19], whose dynamics is strongly slow down in their hydration shell [15,20,21,22]. Recently, disaccharides were shown to decrease the flexibility of lysozyme [17,23], thereby reducing its conformational entropy.…”
Section: -Introductionmentioning
confidence: 99%